Sistem Otomatisasi Sirkulasi dan Penggantian air Kolam Menggunakan Arduino Uno untuk Peternakan Ikan di Sukabangun Kabupaten Ketapang - Syarif Ishak Alkadri; Yudi Chandra (Energi & Kelistrikan, 2019)
This tool detects turbidity by paying attention to the resistance value on the LDR sensor that is the less light received by the LDR sensor, the higher the resistance so that at some level will appear on the LCD whether classified as turbid, very turbid, clear or very clear. While the drain pump will work if the water is considered unhealthy for fish, for example, turbid water is even very turbid and the pump will die if the ultrasonic sensor has got the maximum distance ie in this system it is> 21 cm Filling pump will work if pump 1 is dead and will die if has reached the minimum distance of <= 7 cm. While for the PH value can be seen through a probe dipped in the pool and the results can be known on the LCD, if the water is detected to have an abnormal PH then the pump will drain automatically until the water PH state becomes normal and the automatic feeder system is by adjusting the delay of the servo motor. From the tests carried out, it was found that this tool can detect the level of turbidity of water whether the water is classified as very turbid, turbid, less clear, clear and if what is detected is very turbid then the pump will drain and refill automatically. This tool can also detect the PH value of water which will command the drain pump to work if the water PH is not normal as programmed. and can feed automatically whether 3,4,5 or 6 times a day.